Perkembangan Pembelajaran Bahasa Indonesia dan Upaya Penguatannya dalam Sistem Pendidikan Nasional - Azmah, Siti Fatimah Nur (Indonesian Journal of Applied Linguistics Review, 2023)
This study aims to determine the development of Indonesian language learning and efforts to strengthen it in the national education system. This research is a type of qualitative descriptive research using the library research method (literature study), looking for sources of relevant literature according to the topics discussed, with the aim of finding scientific and theoretical studies. This study uses data analysis techniques which consist of three stages, namely (1) Organize, at this stage grouping the literature studied. Literature must first be reviewed before being used, so that it is in accordance with the subject matter. (2) Synthesize, at this stage, combines the results of grouping literature in a concise and cohesive manner. (3) Identify, at this stage identify issues that are relevant and important to study and analyze, in order to produce scientific paragraphs. From the description of the results of the data analysis, it can be concluded that the development of Indonesian language learning in Indonesia continues to change according to the curriculum used. Starting from the 1947 curriculum to the independent curriculum currently used in schools. Strengthening the Indonesian language in the national education system includes language that educates the life of the nation and the position and function of the Indonesian language.